Lithium-rich lithium ferrite material as well as preparation method and application thereof

By doping aluminum elements in lithium-rich lithium ferrate and forming a carbon cladding layer, the problem of lithium ion loss during the first charging process of lithium-ion batteries is solved, the high-temperature storage and room-temperature cycling performance of the battery is improved, and higher electrochemical performance and safety are achieved.

CN119725530APending Publication Date: 2025-03-28SHENZHEN YANYI NEW MATERIALS CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202311261774.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the first charging process, the existing lithium-ion batteries have an irreversible lithium-containing passivation film formed on the negative electrode surface, resulting in loss of active lithium and reducing the available energy of the battery. The existing lithium supplement technology has problems with poor chemical stability and safety hazards of lithiation reagents.

Method used

Doped lithium-rich lithium ferrate material is used as the lithium supplement additive for the positive electrode active material. By doping aluminum elements in lithium-rich lithium ferrate, a lithium-aluminum compound with a more stable structure is formed, and a carbon cladding layer is formed on the surface of the material to improve conductivity and structural stability.

Benefits of technology

Improve the high-temperature storage performance and room-temperature circulation performance of lithium-ion batteries, improve the safety and electrochemical performance of batteries, and meet the design requirements of high-specific capacity lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725530A_ABST
    Figure CN119725530A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-rich lithium ferrite material and a preparation method and application thereof, the lithium-rich lithium ferrite material comprises a core layer and a carbon coating layer, the core layer is doped lithium-rich lithium ferrite, the chemical formula of the doped lithium-rich lithium ferrite is Li < 5 > Fe < 1-x > Al < x > O < 4 >, and x is 0.003-0.030. The lithium-rich lithium ferrite material is high in structural stability and excellent in conductivity; as a lithium supplement additive of a positive electrode active material, the composite material can improve electrochemical performance such as high-temperature storage performance and normal-temperature cycle performance of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials and relates to a lithium-rich lithium ferrite material and a preparation method and application thereof. Background Art

[0002] As a new type of high-energy battery, lithium-ion batteries are widely used in small devices such as mobile communication devices, portable computers, camcorders, cameras, MP3s, etc. They are also used as reserve power sources for solar and wind power generation systems, cordless power tools, and hybrid electric vehicles (HEVs) and pure electric vehicles (EVs). In particular, with the rapid growth in demand for lithium-ion batteries in electric vehicles and solar and wind energy storage, high requirements are placed on the safety, cycle performance, rate performance, and high and low temperature performance of lithium-ion batteries.

[0003] In order to meet the design requirements of high specific capacity lithium batteries, the most effective way is to select high specific capacity positive and negative electrode materials, such as silicon, tin, aluminum, oxides, etc. as new negative electrode materials. However, during the first charging of lithium batteries, part of the lithium released from the positive electrode forms an irreversible lithium-containing passivation film (SEI) on the surface of the negative electrode, causing active lithium loss, thereby reducing the available energy of the battery.

[0004] In order to make up for this part of lithium loss, the current practice is to pre-replenish lithium to the positive or negative electrode. Negative electrode lithium replenishment generally involves reacting metallic lithium powder, foil, or sheet with negative electrode materials. However, this method has problems such as poor chemical stability of the lithium reagent and greater safety hazards of active lithium powder. Positive electrode lithium replenishment generally involves mixing the lithium replenishment additive with the positive electrode material in proportion, and making a battery cell after slurry adjustment. During the first charging process, excess lithium is released to replenish the lithium consumed by the formation of the SEI film on the negative electrode surface, thereby completing the lithium replenishment. Compared with negative electrode lithium replenishment, positive electrode lithium replenishment technology does not require changes to the existing battery production process, and therefore has the characteristics of low cost, simplicity, high safety, and more industrial application prospects.

[0005] A representative substance in positive electrode lithium supplement additives is lithium-rich lithium iron oxide (Li5FeO4). The lattice structure of lithium-rich lithium iron oxide is unstable. Oxygen is generated during the delithiation process. The strongly oxidizing oxygen atoms react with the electrolyte to cause serious gas production, affecting the safety and electrochemical performance of the battery. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a lithium-rich lithium iron oxide material and a preparation method and application thereof. The lithium-rich lithium iron oxide material has high structural stability and excellent conductivity. As a lithium supplement additive for positive electrode active materials, it can improve the electrochemical properties of lithium-ion batteries such as high-temperature storage performance and room-temperature cycle performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a lithium-rich iron oxide material, wherein the lithium-rich iron oxide material comprises a core layer and a carbon coating layer, wherein the core layer is a doped lithium-rich iron oxide, and the chemical formula of the doped lithium-rich iron oxide is Li5Fe 1- x Al x O4, x is 0.003 to 0.030, wherein x can be 0.003, 0.004, 0.005, 0.006, 0.008, 0.010, 0.015, 0.020, 0.025 or 0.030, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0009] In the present invention, aluminum is doped into lithium-rich lithium ferrite, and the lithium-aluminum compound Li5AlO4 formed by the combination of aluminum and lithium has a crystal structure similar to that of lithium ferrite. Without removing lithium, the structure of lithium-rich lithium ferrite is more stable, the degree of side reaction with the electrolyte is improved, and severe gas production is avoided.

[0010] As a preferred technical solution of the present invention, the carbon coating layer accounts for 0.2-2.0wt% of the total mass of the lithium ferrite-rich material, and in some embodiments, it is 1.0-2.0wt%, for example, 0.2wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] In the present invention, the carbon coating layer prevents the doped lithium-rich iron oxide in the core layer from contacting the external environment, thereby improving the stability and safety of the lithium-rich iron oxide material, and at the same time improving the conductivity of the material and reducing the internal resistance, which is conducive to the efficient lithium supplementation effect. If the mass proportion of the carbon coating layer is too high, it is easy to reduce the Fe element in the lithium-rich iron oxide material, and the carbon coating layer and the residual lithium on the surface generate impurity lithium carbonate, which affects the purity of the material and reduces the battery capacity; if the mass proportion is too low, it will not have the effect of improving the conductivity.

[0012] As a preferred technical solution of the present invention, the particle size of the lithium-rich lithium ferrite material is 5 to 15 μm, such as 6 μm, 8 μm, 10 μm, 12 μm or 14 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] In the present invention, the carbon coating layer is obtained by gas-phase coating of a carbon source; the carbon source includes any one of methane, ethane, propane, ethylene, propylene, butene or acetylene, or a combination of at least two thereof.

[0014] In a second aspect, the present invention provides a method for preparing the lithium-rich lithium ferrite material as described in the first aspect, the preparation method comprising the following steps:

[0015] (1) mixing a lithium source, an iron source, and an aluminum source, and sintering to obtain the doped lithium-rich lithium iron oxide;

[0016] (2) The doped lithium-rich iron phosphate material of step (1) is crushed and then gas-phase carbon-coated with a carbon source to obtain the lithium-rich iron phosphate material.

[0017] In the present invention, the preparation method incorporates the doping element aluminum during the synthesis process, generates a structurally stable lattice from the synthesis process, and improves the structural stability of the material; and then combines carbon coating to improve the conductivity, which can greatly improve the electrical properties of the material. The combination of the two steps can expand the comprehensive advantages of the material. The lithium-rich lithium iron oxide material as an additive for the positive electrode active material can improve the electrochemical properties of lithium-ion batteries such as high-temperature storage performance and room-temperature cycle performance.

[0018] As a preferred technical solution of the present invention, the lithium source in step (1) includes any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate or lithium phosphate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of lithium oxide and lithium hydroxide, a combination of lithium hydroxide and lithium carbonate, a combination of lithium carbonate and lithium chloride, a combination of lithium chloride and lithium nitrite, a combination of lithium nitrite and lithium nitrate, a combination of lithium nitrate and lithium oxalate, a combination of lithium oxalate and lithium acetate, a combination of lithium acetate and lithium phosphate, or a combination of lithium hydroxide, lithium chloride and lithium oxalate, etc.

[0019] As a preferred technical solution of the present invention, the iron source in step (1) includes any one of ferric chloride, ferric oxide, ferric oxide, ferric hydroxide, ferric oxyhydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate or ferric formate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of ferric chloride and ferric oxide, a combination of ferric oxide and ferric oxide, a combination of ferric oxide and ferric hydroxide, a combination of ferric oxide and ferric nitrate, a combination of ferric nitrate and ferric acetate, a combination of ferric acetate and ferric citrate, a combination of ferric citrate and ferric phosphate, a combination of ferric phosphate and ferrous oxalate, a combination of ferrous oxalate and ferrous formate, or a combination of ferric chloride, ferric hydroxide and ferric citrate, etc.

[0020] As a preferred technical solution of the present invention, the aluminum source in step (1) includes any one of aluminum oxide, aluminum hydroxide or aluminum chloride, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of aluminum oxide and aluminum hydroxide, a combination of aluminum hydroxide and aluminum chloride, a combination of aluminum chloride and aluminum oxide, or a combination of aluminum oxide, aluminum hydroxide and aluminum chloride, etc.

[0021] As a preferred technical solution of the present invention, in step (1), the molar ratio of the lithium element in the lithium source, the iron element in the iron source and the aluminum element in the aluminum source is 5:(0.997-0.97):(0.003-0.03), such as 5:0.995:0.005, 5:0.992:0.008, 5:0.99:0.01, 5:0.985:0.015, 5:0.98:0.2, 5:0.975:0.025, 5:0.995:0.025, 5:0.992:0.2, 5:0.99:0.015, 5:0.985:0.01, 5:0.98:0.008 or 5:0.975:0.005, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. When the molar amount of iron is too much, the molar amount of lithium is insufficient, resulting in a low capacity of the lithium-rich iron oxide material; when the molar amount of iron is too little, the molar amount of lithium is excessive, absorbing water in the air, resulting in an increase in residual alkali and a decrease in processing performance. When the molar amount of aluminum is too much, it will become an impurity and affect the purity of the material; when the molar amount of aluminum is too little, a stable lattice cannot be generated.

[0022] Preferably, the sintering in step (1) is carried out in a protective atmosphere or an oxidizing atmosphere. The protective atmosphere includes any one of a nitrogen atmosphere, an argon atmosphere, a helium atmosphere, a xenon atmosphere, a radon atmosphere or a neon atmosphere, or a combination of at least two thereof. The oxidizing atmosphere includes an oxygen atmosphere and / or an air atmosphere.

[0023] Preferably, the sintering in step (1) includes a first sintering and a second sintering performed sequentially. The temperature of the second sintering is higher than the temperature of the first sintering. In the present invention, the two-stage sintering can further improve the degree of reaction, improve the purity of the material, reduce the residual alkali, and make the material structure more stable.

[0024] Preferably, the first sintering is sintering at 100-250° C. for 0.5-4 h.

[0025] Preferably, the second sintering is performed at 600-900° C. for 5-20 hours.

[0026] As a preferred technical solution of the present invention, the pulverization treatment in step (2) is carried out in a protective atmosphere. The protective atmosphere can be any one of nitrogen atmosphere, argon atmosphere, helium atmosphere, xenon atmosphere, radon atmosphere or neon atmosphere, or a combination of at least two thereof.

[0027] Preferably, the pulverization in step (2) is followed by sieving, and the average particle size of the powder obtained after the sieving is 5-15 μm, such as 6 μm, 8 μm, 10 μm or 14 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. The sieving can be performed using a sieve with a mesh size of 400 to 500 meshes.

[0028] In the present invention, the doped lithium-rich lithium ferrite obtained in step (1) is pulverized because the material is in block form after sintering and needs to be crushed into powder before the next carbon coating process can be carried out.

[0029] Preferably, the gas phase carbon coating in step (2) is performed in a protective atmosphere. The protective atmosphere can be any one of nitrogen atmosphere, argon atmosphere, helium atmosphere, xenon atmosphere, radon atmosphere or neon atmosphere, or a combination of at least two thereof.

[0030] Preferably, the carbon source includes any one or a combination of at least two of methane, ethane, propane, ethylene, propylene, butene or acetylene.

[0031] Preferably, the temperature of the gas phase carbon coating is 700-1000° C., and the time of the gas phase carbon coating is 1.0-3.0 h.

[0032] The present invention performs gas-phase carbon coating on the carbon source gas to obtain a carbon coating layer deposited on the surface of the doped lithium-rich ferrite, so that the lithium-rich ferrite material has high structural stability, low residual alkali content, and improved conductivity.

[0033] In a third aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising the lithium-rich iron oxide material as described in the first aspect or the lithium-rich iron oxide material obtained by the preparation method of the lithium-rich iron oxide material as described in the first aspect. The lithium-rich iron oxide material can be used as an additive for the positive electrode active material of a lithium-ion battery.

[0034] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] The invention provides a lithium-rich lithium iron oxide material. The lithium-rich lithium iron oxide material has high structural stability, high purity and low residual alkali value, the purity is ≥96%, the residual alkali value is ≤4%, and the processing performance is good. The material has a carbon coating layer so that the conductivity is excellent. The lithium-rich lithium iron oxide material is used as a lithium supplement additive for positive electrode active materials, and can improve the electrochemical properties of lithium-ion batteries such as high-temperature storage performance and room-temperature cycle performance. After fully charged storage at high temperature of 60°C for 7 days, the thickness change rate is <3.6%, and the capacity retention rate of 600 room-temperature cycles is ≥97.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the X-ray diffraction pattern of the lithium-rich lithium ferrite material prepared in Example 3;

[0038] Figure 2 is the SEM spectrum of the lithium-rich lithium iron oxide material prepared in Example 3;

[0039] Figure 3 This is the first charge and discharge curve of a soft-pack battery prepared using the lithium iron-rich lithium prepared in Example 3 as an additive for the positive electrode active material.

[0040] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0042] Example 1

[0043] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, the preparation method comprising the following steps:

[0044] (1) 747.03 g (25 mol) of lithium oxide, 796.04 g (4.985 mol) of ferric oxide, and 1.53 g (0.015 mol) of aluminum oxide are mixed in a mixer to obtain a mixed raw material; in a nitrogen atmosphere, the mixed raw material is heated to 100° C., kept at this temperature for 4.0 h, and subjected to a first sintering, and then heated to 600° C., kept at this temperature for 20.0 h, and subjected to a second sintering, and then naturally cooled to 25° C. to obtain lithium iron oxide rich in aluminum doped with aluminum;

[0045] (2) The aluminum-doped lithium iron oxide described in step (1) is crushed in a nitrogen atmosphere and sieved using a 400-mesh screen; in a nitrogen atmosphere, the crushed and sieved aluminum-doped lithium iron oxide powder is placed in a chemical vapor deposition furnace, heated to 700°C, charged with acetylene for 3.0 hours, then the acetylene is stopped, and the temperature is lowered to room temperature to obtain a lithium iron oxide material with a carbon coating layer deposited on the surface. The lithium iron oxide material includes a core layer and a carbon coating layer, the core layer is a doped lithium iron oxide, and the chemical formula of the doped lithium iron oxide is Li5Fe 0.997 Al 0.003 O4, the carbon coating layer accounts for 1.13wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 14.8μm.

[0046] Example 2

[0047] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, the preparation method comprising the following steps:

[0048] (1) 747.03 g (25 mol) of lithium oxide, 774.49 g (4.85 mol) of ferric oxide, and 15.29 g (0.15 mol) of aluminum oxide are mixed in a mixer to obtain a mixed raw material; in a nitrogen atmosphere, the mixed raw material is heated to 250° C., kept at this temperature for 0.5 h, and subjected to a first sintering, and then heated to 900° C., kept at this temperature for 5.0 h, and subjected to a second sintering, and then naturally cooled to 15° C. to obtain lithium iron oxide rich in aluminum doped therewith;

[0049] (2) The aluminum-doped lithium iron oxide described in step (1) is crushed in a nitrogen atmosphere and sieved using a 500-mesh screen; in a nitrogen atmosphere, the crushed and sieved aluminum-doped lithium iron oxide powder is placed in a chemical vapor deposition furnace, heated to 1000°C, charged with acetylene for 1.0h, then the acetylene is stopped, and the temperature is lowered to room temperature to obtain a lithium iron oxide material with a carbon coating layer deposited on the surface. The lithium iron oxide material includes a core layer and a carbon coating layer, the core layer is a doped lithium iron oxide, and the chemical formula of the doped lithium iron oxide is Li5Fe 0.97 Al 0.03 O4, the carbon coating layer accounts for 1.82wt% of the total mass of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 6.5μm.

[0050] Example 3

[0051] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, the preparation method comprising the following steps:

[0052] (1) 747.03 g (25 mol) of lithium oxide, 790.46 g (4.95 mol) of ferric oxide, and 5.10 g (0.05 mol) of aluminum oxide are mixed in a mixer to obtain a mixed raw material; in a nitrogen atmosphere, the mixed raw material is heated to 175° C., kept at this temperature for 2.5 h, and subjected to a first sintering, and then heated to 750° C., kept at this temperature for 12.0 h, and subjected to a second sintering, and then naturally cooled to 20° C. to obtain lithium iron oxide rich in aluminum doped with aluminum;

[0053] (2) The aluminum-doped lithium iron oxide described in step (1) is crushed in a nitrogen atmosphere and sieved using a 425-mesh screen; in a nitrogen atmosphere, the crushed and sieved aluminum-doped lithium iron oxide powder is placed in a chemical vapor deposition furnace, heated to 850°C, charged with acetylene for 1.5 hours, then the acetylene is stopped, and the temperature is lowered to room temperature to obtain a lithium iron oxide material with a carbon coating layer deposited on the surface. The lithium iron oxide material includes a core layer and a carbon coating layer, the core layer is a doped lithium iron oxide, and the chemical formula of the doped lithium iron oxide is Li5Fe 0.99 Al 0.01 O4, the carbon coating layer accounts for 1.85wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 10.1μm.

[0054] from Figure 1 The X-ray diffraction pattern shows that the mass ratio of Al doped in Example 3 is consistent with that of Li5Fe 1-x Al x When O4, x is 0.003-0.030, it has no effect on the peak shape and the material maintains high purity.

[0055] from Figure 2 From the SEM images, it can be seen that the normal doping and coating products of Example 3 have uniform particles and a smooth surface.

[0056] Example 4

[0057] In this embodiment, except that the raw materials in step (1) are replaced by 1197.42 g (50 mol) of lithium hydroxide, 1058.01 g (9.9 mol) of ferric hydroxide, and 7.80 g (0.1 mol) of aluminum hydroxide, the other conditions are the same as those in Example 3.

[0058] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.99 Al 0.01 O4, the carbon coating layer accounts for 1.80wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 9.7μm.

[0059] Example 5

[0060] In this embodiment, except that the raw materials in step (1) are replaced by 1847.38 g (25 mol) of lithium carbonate, 764.06 g (3.3 mol) of ferrosoferric oxide, and 13.33 g (0.1 mol) of aluminum chloride, and the sintering atmosphere in step (1) is replaced by air atmosphere, the other conditions are the same as those in Example 3.

[0061] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.99 Al 0.01 O4, the carbon coating layer accounts for 1.87wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 11.4μm.

[0062] Example 6

[0063] In this example, except that the carbon source gas acetylene in step (2) is replaced by ethylene, the other conditions are the same as those in Example 3.

[0064] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.99 Al 0.01 O4, the carbon coating layer accounts for 1.54wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 10.6μm.

[0065] Example 7

[0066] In this embodiment, except that the carbon source gas acetylene in step (2) is replaced by methane and the gas phase carbon coating time is 3 hours, the other conditions are the same as those in Example 3.

[0067] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.99 Al 0.01 O4, the carbon coating layer accounts for 1.97wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 11.0μm.

[0068] Example 8

[0069] In this embodiment, except that the molar amount of the raw materials in step (1) is replaced by 747.03g (25mol) lithium oxide, 796.04g (4.985mol) ferric oxide, and 1.53g (0.015mol) aluminum oxide, and the sintering atmosphere in step (1) is replaced by air atmosphere, the other conditions are the same as those in Example 3.

[0070] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.997 Al 0.003 O4, the carbon coating layer accounts for 1.78wt% of the total mass of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 11.2μm.

[0071] Example 9

[0072] In this embodiment, except that the molar amount of the raw materials in step (1) is replaced by 747.03g (25mol) lithium oxide, 794.45g (4.975mol) ferric oxide, and 2.55g (0.025mol) aluminum oxide, and the sintering atmosphere in step (1) is replaced by air atmosphere, the other conditions are the same as those in Example 3.

[0073] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.995 Al 0.005 O4, the carbon coating layer accounts for 1.81wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 10.7μm.

[0074] Example 10

[0075] In this embodiment, except that the molar amount of the raw materials in step (1) is replaced by 747.03g (25mol) lithium oxide, 782.47g (4.9mol) ferric oxide, and 10.20g (0.1mol) aluminum oxide, and the sintering atmosphere in step (1) is replaced by air atmosphere, the other conditions are the same as those in Example 3.

[0076] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.98 Al 0.02 O4, the carbon coating layer accounts for 1.83wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 11.0μm.

[0077] Embodiment 11

[0078] In this embodiment, except that the molar amount of the raw materials in step (1) is replaced by 747.03g (25mol) lithium oxide, 774.49g (4.85mol) ferric oxide, and 15.29g (0.15mol) aluminum oxide, and the sintering atmosphere in step (1) is replaced by air atmosphere, the other conditions are the same as those in Example 3.

[0079] The obtained lithium-rich iron oxide material includes a core layer and a carbon coating layer. The core layer is doped lithium-rich iron oxide. The chemical formula of the doped lithium-rich iron oxide is Li5Fe 0.97 Al 0.03 O4, the carbon coating layer accounts for 1.74wt% of the total weight of the lithium ferrite material. The particle size D50 measured by a laser particle size analyzer is 11.5μm.

[0080] Comparative Example 1

[0081] In this comparative example, except that aluminum oxide was not added in step (1) but was replaced with an equal molar amount of iron oxide, the other conditions were the same as those in Example 3.

[0082] Comparative Example 2

[0083] In this comparative example, except that the molar amounts of the raw materials in step (1) are replaced by 747.03 g (25 mol) of lithium oxide, 758.52 g (4.75 mol) of ferric oxide, and 25.49 g (0.25 mol) of aluminum oxide, the other conditions are the same as those in Example 3.

[0084] Comparative Example 3

[0085] In this comparative example, except that the aluminum oxide in step (1) is replaced by an equal molar amount of cobalt oxide, the other conditions are the same as those in Example 3.

[0086] Comparative Example 4

[0087] In this comparative example, except that the aluminum oxide in step (1) is replaced by an equal molar amount of manganese oxide, the other conditions are the same as those in Example 3.

[0088] Comparative Example 5

[0089] In this comparative example, except that the aluminum oxide in step (1) is replaced by an equal molar amount of lanthanum oxide, the other conditions are the same as those in Example 3.

[0090] Comparative Example 6

[0091] In this comparative example, except that the aluminum oxide in step (1) is replaced by an equal molar amount of cadmium oxide, the other conditions are the same as those in Example 3.

[0092] Comparative Example 7

[0093] In this comparative example, except that step (2) is not subjected to gas phase carbon coating, the other conditions are the same as those of Example 3.

[0094] Comparative Example 8

[0095] In this comparative example, the carbon source gas acetylene in step (2) is replaced by solid carbon source glucose, and the other conditions are the same as those in Example 3.

[0096] The performance parameters of the prepared lithium-rich lithium iron oxide material are as follows:

[0097] ①Basic property test of lithium-rich lithium iron oxide materials

[0098] The purity, residual alkali value, carbon content, powder resistance and moisture content of the lithium-rich lithium ferrite materials prepared in Examples 1-11 and Comparative Examples 1-8 are shown in Table 1.

[0099] Test conditions:

[0100] Purity test: The phase composition is analyzed by XRD, and the component phases are quantitatively refined. The obtained mass fraction is the purity.

[0101] Residual alkalinity value test: Using methanol as solvent, the hydroxyl and carbonate contents of the material are tested and calculated by acid-base titration method, and the total amount of LiOH and Li2CO3 is calculated.

[0102] Carbon content test: Use carbon sulfur analyzer.

[0103] Powder resistance test: Use a powder resistance meter.

[0104] Moisture test: Use Karl Fischer titrator.

[0105] ②X-ray diffraction analysis and morphology analysis

[0106] X-ray diffraction analysis was performed on Example 3, and the specific conditions were: scanning rate 10 degrees / min, scanning range 10-90 degrees.

[0107] ③Battery performance test:

[0108] The preparation method of lithium-ion battery is as follows:

[0109] (1) Lithium iron phosphate LFP, lithium iron oxide materials obtained in Example 1-11 and Comparative Example 1-11, conductive agent SuperP, carbon nanotubes, binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 94:2:1.5:0.5:2 to prepare a positive electrode slurry (solid content of 60%), and a double-sided surface density of 340 g / cm 2 Coated on the current collector aluminum foil, dried at 70°C, cold pressed at 4MPa at room temperature, trimmed, cut, and slit, and then welded to the tabs to make the positive electrode sheet;

[0110] (2) In an inert protective atmosphere, artificial graphite negative electrode material, conductive agent SuperP, adhesive PVDF and NMP are mixed in a mass ratio of 97.5:1.0:1.5 to form a negative electrode slurry (solid content of 50%), which is coated on the current collector copper foil with a thickness of 100 μm, dried at 100° C., cold pressed at 4 MPa at room temperature, and then trimmed, cut and stripped, and the tabs are welded to form a negative electrode sheet;

[0111] (3) Using a PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic shell package and placed under a relative vacuum pressure of -0.95×10 5 Pa, dried at 100 ° C to a moisture content of less than 100 ppm. The electrolyte is injected into the dried bare battery, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (concentration 1.0M), and is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity division) to make a soft-pack lithium-ion battery.

[0112] Test conditions:

[0113] First charge and discharge capacity test: The battery prepared above was formed and divided using a battery test cabinet. The formation process was to charge at a constant current of 0.05C for 2.0h, then at a constant current of 0.15C for 2.5h, then at a constant current of 0.33C to 4.1V, and then at a constant voltage of 4.1V to a cut-off current of 0.02C; for the divided capacity, discharge at 0.33C to 2.5V; and calculate the first discharge specific capacity.

[0114] Normal temperature cycle performance test: At 25°C, charge the battery to 3.7V at 0.5C constant current and constant voltage, cut off current 0.02C, leave for 5 minutes, then discharge to 2.5V at 1C constant current, leave for 5 minutes. After 600 cycles of charge / discharge, calculate the 600th cycle capacity retention rate. The calculation formula is as follows:

[0115] 600th cycle capacity retention rate (%)=(600th cycle discharge capacity / 1st cycle discharge capacity)×100%.

[0116] High temperature storage gas generation test: For the batteries that have undergone the initial charge and discharge test, recharge them at 0.33C to 3.65V, place them in a constant temperature oven at 60°C for 7 days, and test the thickness change rate of the soft pack before and after standing.

[0117] The test results of the battery performance are shown in Table 2.

[0118] Table 1

[0119]

[0120]

[0121] Table 2

[0122]

[0123]

[0124] analyze:

[0125] It can be seen from Table 1-2 that the lithium-rich lithium iron oxide material prepared by Example 1-11 has a purity ≥96% and a residual alkali value ≤4%. The lithium-rich lithium iron oxide material is used as a lithium supplement additive for positive electrode active materials, which can improve the electrochemical properties of lithium-ion batteries such as high temperature storage performance and room temperature cycle performance. After being fully charged and stored at 60°C for 7 days, the thickness change rate is <3.6%, and the capacity retention rate of 600 room temperature cycles is ≥97.3%.

[0126] The data results of Example 3 and Examples 8-11 show that as the molar ratio of the aluminum element in the raw aluminum source increases, the improvement effect on the high-temperature storage thickness change rate increases.

[0127] The data results of Example 3 and Comparative Example 1 show that the thickness change rate during high-temperature storage increases significantly when no aluminum source is doped in the raw material.

[0128] The data results of Example 3 and Comparative Example 2 show that too much aluminum source is doped in the raw material, which affects the purity and reduces the capacity.

[0129] The data results of Example 3 and Comparative Examples 3-6 show that doping with other metal elements can improve the high-temperature storage thickness change rate to a certain extent, but the effect is not as good as that of doping with Al.

[0130] The data results of Example 3 and Comparative Example 7 show that the conductivity of lithium-rich ferrite is reduced and the capacity is low when there is no carbon coating layer.

[0131] The data results of Example 3 and Comparative Example 8 show that the solid-phase carbon source has limited effect on improving the conductivity of lithium-rich lithium ferrite, and the capacity is slightly low.

[0132] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium-rich lithium iron oxide material, characterized in that: The lithium-rich iron oxide material comprises a core layer and a carbon coating layer, wherein the core layer is a doped lithium-rich iron oxide, and the chemical formula of the doped lithium-rich iron oxide is Li5Fe 1-x Al x O4, x is 0.003~0.

030.

2. The lithium iron oxide material according to claim 1, characterized in that: The carbon coating layer accounts for 0.2-2.0 wt% of the total mass of the lithium iron oxide-rich material; Preferably, the particle size of the lithium ferrite-rich lithium material is 5 to 15 μm.

3. A method for preparing the lithium-rich lithium ferrite material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a lithium source, an iron source and an aluminum source, and sintering to obtain the doped lithium-rich lithium ferrite; (2) The doped lithium-rich iron phosphate described in step (1) is crushed and then gas-phase carbon-coated with a carbon source to obtain the lithium-rich iron phosphate material.

4. The preparation method according to claim 3, characterized in that: The lithium source in step (1) comprises any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate or lithium phosphate, or a combination of at least two thereof; Preferably, the iron source in step (1) comprises any one of ferric chloride, ferroferric oxide, ferric oxide, ferric hydroxide, ferric oxyhydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate or ferric formate, or a combination of at least two thereof.

5. The preparation method according to claim 3, characterized in that: The aluminum source in step (1) includes any one of aluminum oxide, aluminum hydroxide or aluminum chloride, or a combination of at least two of them.

6. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of lithium in the lithium source, iron in the iron source and aluminum in the aluminum source is 5:(0.997-0.97):(0.003-0.03); Preferably, the sintering in step (1) includes a first sintering and a second sintering; the temperature of the second sintering is higher than the temperature of the first sintering.

7. The preparation method according to claim 3, characterized in that: The pulverization process in step (2) is carried out in a protective atmosphere.

8. The preparation method according to claim 3, characterized in that: The gas phase carbon coating in step (2) is carried out in a protective atmosphere; Preferably, the carbon source includes any one or a combination of at least two of methane, ethane, propane, ethylene, propylene, butene or acetylene.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the lithium-rich lithium ferrite material as claimed in claim 1 or 2 or the lithium-rich lithium ferrite material obtained by the preparation method of the lithium-rich lithium ferrite material as claimed in any one of claims 3 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.

Citation Information

Cited By

  • Composite coated high-performance lithium-rich lithium ferrite material as well as preparation method and application thereof

    CN120749155A

  • Multi-element lithium supplement agent, preparation method thereof, positive pole piece and lithium ion battery

    CN120914367A

  • A multi-element lithium supplementing agent, a preparation method thereof, and a positive electrode sheet and a lithium ion battery

    CN120914367B

  • Low-gas-production lithium-rich lithium ferrite material as well as synthesis method and application thereof

    CN121202197A

  • Lithium-rich material, preparation method thereof, positive pole piece containing lithium-rich material, secondary battery and electric device

    CN121331832A